Decolourisation of Reactive Orange 16 (RO16) dye by free and Immobilized Bacillus UMKDG-1 cells in batch culture - NorHisam, Mubarak Ali (2020)
Increasing demand for textiles cause an increase of production in textile industry all over the world. Higher production of dyed textiles also increases the volume of textile effluent which contains various type of synthetic dyes. Synthetic dye contained many toxic and hazardous materials which give bad effect to nature. There are several types of treatment to treat textile effluent, but all of the treatment is not cost effective, which brings to biological treatments as it is more cost effective. The purpose of this study is to determine the decolourisation of Reactive Orange 16 by dye degrading bacteria, Bacillus UMKDG-1 (free and immobilized cell). The decolourisation of Reactive Orange 16 was carried out using 0.01% (w/v), 0.02% (w/v) and 0.03% (w/v) concentration of Reactive Orange 16. As the study shown, 0.01% (w/v) Reactive Oren 16 obtained the highest percentage of decolourisation. The result for decolourisation of 0.01% (w/v), 0.02% (w/v) and 0.03% (w/v) Reactive Orange 16 by free Bacillus UMKDG-1 cells are 95.38%, 92.50% and 89.93% respectively. However, for decolourisation of 0.01% (w/v), 0.02% (w/v) and 0.03% (w/v) Reactive Orange 16 by immobilized Bacillus UMKDG-1 is lower which are 93.24%, 49.33% and 31.29% respectively.